Students"™ Perception of the Use of Watching Korean Dramas with English Subtitles for Vocabulary Learning - Masduqi, Harits; Khairunnisa, Siti (Journal of English Education Program, 2024)
Learning vocabulary can be accomplished not only by watching English movies, but also by watching Korean dramas. This research aimed to explore students' perceptions of the use of watching Korean dramas with English subtitles for vocabulary learning. Learning vocabulary can be accomplished enjoyably by watching Korean dramas with English subtitles. The students freely chose the Korean dramas they wanted to watch and learned new words through them. The participants were the eleventh-grade science students. Before collecting the data, the students were assigned to watch Korean dramas for two weeks as an independent study. The data were obtained from an online questionnaire that was distributed through a WhatsApp group. This showed that the majority of students had a positive perception of watching Korean dramas with English subtitles. They felt improvement in vocabulary mastery, including recognizing spelling and word usage. Students agreed that learning vocabulary by watching Korean Dramas with English subtitles was fun and motivated them to learn English vocabulary.